2017
DOI: 10.1038/cr.2017.34
|View full text |Cite
|
Sign up to set email alerts
|

Blocking the recruitment of naive CD4+ T cells reverses immunosuppression in breast cancer

Abstract: The origin of tumor-infiltrating Tregs, critical mediators of tumor immunosuppression, is unclear. Here, we show that tumor-infiltrating naive CD4+ T cells and Tregs in human breast cancer have overlapping TCR repertoires, while hardly overlap with circulating Tregs, suggesting that intratumoral Tregs mainly develop from naive T cells in situ rather than from recruited Tregs. Furthermore, the abundance of naive CD4+ T cells and Tregs is closely correlated, both indicating poor prognosis for breast cancer patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
143
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(153 citation statements)
references
References 56 publications
9
143
1
Order By: Relevance
“…In particular, we show that clonal neoantigens are associated with infiltration of CTLs and Tregs, while Th2 cells and CAFs are enriched in tumours with lower clonal neoantigen loads. These findings support recent evidence suggesting that differentiation of naïve CD4+ T-lymphocytes into Tregs occurs within tumours 83 , since a microenvironment favouring differentiation into Tregs would likely be selected for in tumours with increased neoantigens and more infiltrating CTLs. Why these relationships between neoantigen loads and T-lymphocytes are apparent only when one considers clonal neoantigens is an intriguing question.…”
Section: Discussionsupporting
confidence: 89%
“…In particular, we show that clonal neoantigens are associated with infiltration of CTLs and Tregs, while Th2 cells and CAFs are enriched in tumours with lower clonal neoantigen loads. These findings support recent evidence suggesting that differentiation of naïve CD4+ T-lymphocytes into Tregs occurs within tumours 83 , since a microenvironment favouring differentiation into Tregs would likely be selected for in tumours with increased neoantigens and more infiltrating CTLs. Why these relationships between neoantigen loads and T-lymphocytes are apparent only when one considers clonal neoantigens is an intriguing question.…”
Section: Discussionsupporting
confidence: 89%
“…An interesting observation is that the two deceased patients belonged to the immune score group that showed a lack of immune cell infiltration in the invasive cancer region. Furthermore, tumors from two of the patients also showed the presence of CD4+ naïve T-cells, which are usually not present in tumor tissue 34 but have earlier been reported in breast cancer samples 35 . Importantly, here we demonstrate that the described methodological approach can be used to dissect many different aspects of the immune-tumor interplay and substantiate whether the lack of immune cell infiltration or type of immune cells in tumor tissue is related to worse prognosis and/or lower overall survival.…”
Section: Discussionmentioning
confidence: 55%
“…Su et al . suggested blocking of naive CD4 + T cell recruitment as an effective mechanism to reverse immunosuppression in breast cancer. Additionally, Plitas et al .…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral T regs are induced from naive T regs via peripheral antigen presentation [21]. Su et al [37] suggested blocking of naive CD4 1 T cell recruitment as an effective mechanism to reverse immunosuppression in breast cancer. Additionally, Plitas et al [38] showed an expansion of suppressive intratumoral T regs in breast cancer with distinct gene expression compared to circulating T regs .…”
Section: F -H -F -H + F + H + F + H -F -H -F -H + F + H + F + Hmentioning
confidence: 99%